L’antropologia di Romano Guardini in Mondo e Persona: Struttura, senso, valore - Ascencio, Juan G. (Alpha omega, 2015)
This article presents a philosophical commentary on the concept of Person developed by Romano Guardini in World and Person (1939), targeting specifically the first two chapters of part II of the book’s which contain the pages with greater philosophical relevance. Special attention is given to the way in which Guardini synthesized elements drawn from anthropological currents such as existentialism, phenomenology, dialogical philosophy and personalism. The commentary seeks to highlight the structure he provides, which ensures the philosophical unity of the section examined. Guardini’s theoretical relation with some of the main thinkers of his day is also considered. The closing section of the article presents a series of comments on some of Guardini’s most valuable anthropological teachings.